Tertiary lymphoid structures and gastric cancer prognosis. Issue 1 (1st November 2022) - Kemi, Niko; Ylitalo, Olli; Väyrynen, Juha P.; Helminen, Olli; Junttila, Anna; Mrena, Johanna; Böhm, Jan; Kauppila, Joonas H.
Abstract : Tertiary lymphoid structures (TLSs) are part of immune response against cancer. Their high density and high diameter have been shown to be associated with prognosis in different cancer types. The aim of this study was to examine the prognostic significance of TLS density and diameter in gastric cancer and reproducibility of their assessments. TLS densities and maximal TLS diameter were assessed from hematoxylin–eosin (HE) stained slides of 721 surgically treated gastric cancer patients from two hospitals in Finland. Mortality hazard ratios (HRs) for TLS densities and maximal TLS diameter were analyzed. TLS densities and maximal TLS diameter were assessed with moderate interobserver agreement (Cohen's kappa 0.50–0.62). Maximal TLS density was not associated with survival (adjusted HR 0.85, 95% CI 0.70–1.02) and neither was hotspot TLS density (adjusted HR 0.85, 95% CI 0.70–1.02). High maximal TLS diameter was associated with longer survival in overall study population (adjusted HR 0.74, 95% CI 0.61–0.89) and in diffuse type subgroup (adjusted HR 0.65, 95% CI 0.50–0.85). In conclusion, high maximal TLS diameter is associated with improved survival in gastric cancer and can be assessed from HE‐stained slides. Its prognostic value might be limited to diffuse histological type.